Results of the investigation of the asteroid (2121) Sevastopol based on photometric observations of mutual phenomena. (1st October 2019) - Sokova, Iraida A.; Sokov, Eugenii N.; Gorshanov, Denis L.; Fernández-Lajús, Eduardo; di Sisto, Romina; Bretton, Marc; Marchini, Alessandro; Vasilkova, Olga O.; Knight, Carl R.; Colazo, Carlos A.; Quiñones, Cecilia; Girardini, Carla
Abstract: The asteroid (2121) Sevastopol is a binary asteroid from the main belt. The duplicity of the asteroid was discovered based on photometric observations of mutual phenomena (eclipses and occultations) that were detected in its light curves (Higgins et al., 2010). We organized a photometrical observational campaign for the observations of mutual phenomena in binary system of the asteroid (2121) Sevastopol and an investigation of the properties of the asteroid's satellite. The observations allowed us to define mass, density, taxonomical class and preliminary orbit of the satellite of the asteroid (2121) Sevastopol. Highlights: The asteroid (2121) Sevastopol is a binary asteroid from the main belt. The duplicity of the asteroid was discovered based on photometric observations of mutual phenomena (eclipses and occultations) that were detected in its light curves (Higgins et al, 2010). We organized a photometrical observational campaign for the observations of mutual phenomena in binary system of the asteroid (2121) Sevastopol asteroid and investigation of properties of the asteroid satellite. The observations allowed us to define mass, density, taxonomical class and preliminary orbit of the satellite of the asteroid (2121) Sevastopol.